2015
DOI: 10.1016/j.renene.2014.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Syngas production from glycerol-dry(CO2) reforming over La-promoted Ni/Al2O3 catalyst

Abstract: A 3 wt% La-promoted Ni/Al2O3 catalyst was prepared via wet co-impregnation technique and physicochemically-characterized. Lanthanum was responsible for better metal dispersion; hence higher BET specific surface area (96.0 m2 g−1) as compared to the unpromoted Ni/Al2O3 catalyst (85.0 m2 g−1). In addition, the La-promoted catalyst possessed finer crystallite size (9.1 nm) whilst the unpromoted catalyst measured 12.8 nm. Subsequently, glycerol dry reforming was performed at atmospheric pressure and temperatures r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 21 publications
4
44
0
Order By: Relevance
“…Combined with the characterization results, it can be clearly observed that the trend of the catalytic performance matches well with that of the active nickel surface areas and nickel metal dispersion. Indeed, the catalytic activity of ESR is highly affected by the amount of Ni sites [75][76][77]. The meso3LaNiAl catalyst exhibits the highest active surface area as shown in Table 1 and hence delivers the highest initial activity.…”
Section: Catalytic Activity In Esrmentioning
confidence: 99%
“…Combined with the characterization results, it can be clearly observed that the trend of the catalytic performance matches well with that of the active nickel surface areas and nickel metal dispersion. Indeed, the catalytic activity of ESR is highly affected by the amount of Ni sites [75][76][77]. The meso3LaNiAl catalyst exhibits the highest active surface area as shown in Table 1 and hence delivers the highest initial activity.…”
Section: Catalytic Activity In Esrmentioning
confidence: 99%
“…Siew et al (2014) investigated the performance of Ni/Al 2 O 3 catalysts doped with La for DRG reaction at 873 K. They found that only 3% La promotion was sufficient to reduce the carbon deposition by 20%. This catalyst composition was also found to display good stability over a 72-h test run at 1023 K at a weight hourly space velocity of 3.6 × 10 -4 ml g -1 h -1 STP (Siew et al, 2015). Kinetic studies showed that glycerol decomposition and glycerol dehydrogenation as the most probably competing route in a parallel pathway for syngas production.…”
Section: Co 2 (Dry) Reforming Of Glycerolmentioning
confidence: 85%
“…For example, Slagtern et al. evaluated Ni/Ln/Al 2 O 3 (Ln=rare earth mixture) catalysts at 800°C and 1 atm, showing that the catalyst with a rare earth content of 10.7 wt% Ln is more active and stable than the unpromoted catalyst . Promoting Al 2 O 3 by Mg can also improve Ni/Al 2 O 3 catalysts.…”
Section: Dry Reforming Of Methanementioning
confidence: 99%